Encouraging Indonesian English Young Learners through Language Games - Tita Ratna Wulandari (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
AbstractIndonesian English Young Learners (IEYL) really close to boredom. Therefore, the teachers are demanded to be as highly creative as possible when they are having classroom activities. To see the recent phenomena, most IEYL feel convenient to study in their English course rather than their school. This is due to the English course provides them with fun, relax, and enjoyable learning environment. In contrast, the school provides the IEYL with monotonous activities. In accordance with this problem, the writer is interested in describing five English games which might be references for school teachers. The problems of this study were: (1) what are the five English games which can help the IEYL in classroom activities? and (2) what are the procedures to apply the games in classroom activities? The findings were descriptively discussed by seeing the literature review. It is found that the games to help IEYL are: (a). Spider Web, (b). Cartoon Color, (c). Find Someone who, (d). Read-Run-Say-Listen-Write, and (e). What is it?Keywords:IEYL, LanguageGames and Classroom Activities